The Blue–Green Edge in Thiruvananthapuram, India: An Initiative for Urban Waterways and Waterfront Developments. Issue 2 (December 2014) - Chandran C. K., Ajai; Gowda, Krishne
<x xml:space="preserve">Abstract</x> Cities seek to reclaim waterfronts while protecting ecosystems and water quality